PENGARUH GOOD CORPORATE GOVERNANCE, KEBIJAKAN DIVIDEN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Octinia, Via (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to examine the influence of the implementation of good corporate governance (GCG),dividend policy (proxy by DPR) and profitability (proxy by ROE) to the companiesâ value (Tobinâs â Q) whichare listed in the Indonesia Stock Exchange and followed by Corporate Governance Perception Index (CGPI) surveyin the observation years of 2009-2012 periods, Dividend Payout Ratio (DPR) and Return on Equity (ROE) whilethe dependent variable uses Tobinâs-Q. The utilization of samples is based on the purposive sampling. The samplesof the research are 8 companies with the observation period from 2009 to 2012. The multiple linear regressions isapplied as the analysis technique. The result of normality test, multicolinearity, autocorrelation andheteroscedasticity show that the regressions model which is free from bias has been fulfilled. The result of theresearch shows that CGPI, DPR and ROE variables are simultaneously have significant influence to the companyvalue. The partial result of the research shows that DPR and ROE variables have significant influence to thecompany value while the CGPI variable has no significant influence to the company value.Keywords: Corporate Governance Perception Index (CGPI), Dividend Payout Ratio (DPR), Return on Equity(ROE), Tobinâs-Q